Does Evidence-Based EU Law Survive the Covid-19 Pandemic? Considering the Status in EU Law of Lockdown Measures Which Affect Free Movement - Davies, Gareth (Frontiers in Human Dynamics, 2020)
When Member States restrict free movement on public health grounds they must show that their measures have a sound scientific basis. However, during the pandemic Member States have imposed a wide variety of restrictions, at the border, and internally. While Member State governments have invariably had local scientific advice, the variety of their measures suggests that their actions have also been driven, to some extent, by public opinion, contrary to what EU law generally allows. This situation could be seen as a defeat for EU law as traditionally conceived, and the triumph of local preferences over scientific standards. Perhaps we learn that in a crisis, local desires for symbolic security and closure trump both law and science. Alternatively, it can be argued that the Court of Justice's emphasis on exclusively objective justifications for measures is unrealistic and over-strict. The pandemic responses show that (i) science is often neither clear nor determinative, and (ii) policy is invariably a mix of science and values, even in apparently technical fields. In either case, the absence of legal challenges to Member State actions leaves free movement in an uncertain state. Have we entered a new phase, where national fears are a more legitimate justification for restricting movement, or will the pandemic be treated as so exceptional as to be beyond law, and thus not a precedent?